A17 Myeloid cell function in mouse models of Huntington's disease. (16th November 2010) - André, R; Schure, U; Magnusson, A; Lahiri, N; Smith, D; Lowdell, M W; Bates, G; Bjorkqvist, M; Tabrizi, S J
Abstract : Background: We have previously described an aberrant innate immune response in Huntington's disease (HD) in which proinflammatory cytokines are increased in HD patient brain striatum, plasma and CSF, and mutant htt expressing myeloid cells produce increased interleukin 6 in response to lipopolysaccharide (LPS). This suggests that altered myeloid cell function may be a key correlate of HD pathogenesis. Moreover, alterations in central nervous system immune cell function appear to be mimicked by those in the periphery, suggesting that monitoring peripheral myeloid cells may provide insights into the potentially pathogenic actions of myeloid cells in the brain. Aims: To examine peripheral myeloid cell function in the R6/2 and Hdh150Q mouse models of HD. Methods: Cytokine production by LPS stimulated myeloid cells was analysed by multiplex ELISA. Myeloid cell function was assessed using specific assays for cell adhesion, differentiation, migration and phagocytosis. Results: Cytokine production by LPS stimulated blood monocytes isolated from 22 month Hdh150Q mice showed a significant increase in the production of proinflammatory cytokines compared with controls. To further characterise these mice, we examined subsets of different Hdh150Q myeloid cell types. Interestingly, the spleens of both 22 month Hdh150Q and 12 week R6/2 mice contain more resting monocytes and fewer MHC II-high cells compared with controls. Further work to characterise the function of peripheral myeloid cell types in terms of adhesion, differentiation, migration and phagocytosis, and to correlate these functional read-outs with those of microglia, the resident myeloid cell of the CNS, is ongoing and will be presented. Conclusions: We demonstrate that peripheral myeloid cells are aberrant in mouse models of HD in a manner similar to that observed in patients. Such studies will provide further insights into the role of myeloid cells and innate immune system dysregulation in HD pathogenesis.